2008
DOI: 10.1128/aac.00964-08
|View full text |Cite
|
Sign up to set email alerts
|

Sitamaquine Sensitivity in Leishmania Species Is Not Mediated by Drug Accumulation in Acidocalcisomes

Abstract: Sitamaquine (WR6026), an 8-aminoquinoline derivative, is a new antileishmanial oral drug. As a lipophilic weak base, it rapidly accumulates in acidic compartments, represented mainly by acidocalcisomes. In this work, we show that the antileishmanial action of sitamaquine is unrelated to its level of accumulation in these acidic vesicles. We have observed significant differences in sitamaquine sensitivity and accumulation between Leishmania species and strains, and interestingly, there is no correlation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 26 publications
0
30
0
1
Order By: Relevance
“…Although mitochondria and acidocalcisomes were initially proposed as SQ targets (43,44), further studies of parasites with acidocalcisomes defective for SQ accumulation showed identical SQ susceptibilities, thus providing clear evidence that the antileishmanial action of SQ is unrelated to its accumulation in acidocalcisomes (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although mitochondria and acidocalcisomes were initially proposed as SQ targets (43,44), further studies of parasites with acidocalcisomes defective for SQ accumulation showed identical SQ susceptibilities, thus providing clear evidence that the antileishmanial action of SQ is unrelated to its accumulation in acidocalcisomes (18).…”
Section: Discussionmentioning
confidence: 99%
“…Entry of SQ into the parasite starts with an electrostatic interaction with anionic phospholipids of the plasma membrane (11). In a seminal work, Vercesi and Docampo (43) observed a loss of mitochondrial electrochemical potential in digitonin-permeabilized parasites after SQ addition, together with alkalinization of acidocalcisomes (44), which also underwent a privileged SQ accumulation, although no correlation was found with its toxicity (18).…”
mentioning
confidence: 99%
“…Late-stage promastigotes from the WT and R4 lines were used to infect mouse peritoneal macrophages from BALB/c mice (Charles River, Ltd.) at a macrophage/parasite ratio of 1:10, as described previously (14). After infection for 6 h, extracellular parasites were removed by washing with serum-free medium.…”
Section: Chemicalmentioning
confidence: 99%
“…Of the new drugs under development, 8-aminoquinolines such as sitamaquine (WR6026; GlaxoSmithKline), which is currently in phase 2b clinical trials (12,34), represent a promising new oral leishmanicidal treatment. Although the mechanism of action of sitamaquine is still unknown, it has been reported that acidocalcisomes play a key role in the accumulation of sitamaquine, although they do not determine the leishmanicidal potency of the drug (14). Other 8-aminoquinolines chemically related to primaquine have been synthesized and evaluated for their antiparasitic activity (1,25).…”
mentioning
confidence: 99%
“…Using a spectrofluorometric assay, we found that the accumulation of TFQ in T. brucei BSF was 50% lower than in promastigotes of L. major (P Ͻ 0.05), this being despite its higher activity against T. brucei. The absence of correlation between susceptibility and uptake level was also reported for the case of sitamaquine, a related 8-aminoquinoline, against different Leishmania species, (25) and for several analogs of the antitrypanosomal diamidines DB75 and DB820 against T. brucei (26).…”
Section: Resultsmentioning
confidence: 99%